A hybrid sliding mode control scheme for rapid earth fault current limiters in compensated distribution networks in bushfire prone areas. Issue 3 (27th February 2023) - Roy, Tushar Kanti; Mahmud, Md Apel; Nasiruzzaman, A B M; Barik, MdAbdul
Abstract: A hybrid sliding mode controller is proposed for rapid earth fault current limiters (REFCLs) used in resonant grounded power distribution networks to self‐extinguish powerline bushfires where the concepts of the proportional integral (PI) action and nonsingular fast terminal sliding surface (NFTSS) are combined together to utilize the benefits of both schemes. A hybrid sliding surface is designed for obtaining the control input so that the fault current compensation is achieved by the residual current compensation (RCC) inverter used within a REFCL to a value that the fire does not ignite. The inclusion of an integral action along with the NFTSS helps to significantly reduce the chattering effect. Furthermore, a continuous function is introduced within the proposed scheme to replace the discontinuous signum function. The switches for the RCC inverter are controlled by deriving control actions from the Lyapunov stability theory applied on the hybrid PI‐NFTSS. The performance of the proposed controller is compared with a nonsingular fast terminal sliding mode controller. For this reason, this paper also includes the design process of nonsingular fast terminal sliding mode controller which is designed using only the NFTSS. Simulations under different scenarios having different fault resistances clearly depict the superiority of the proposed scheme over the nonsingular fast terminal sliding mode controller and an existing integral sliding mode controller in terms of maintaining transient responses. Abstract : A hybrid sliding mode controller is proposed for rapid earth fault current limiters (REFCLs) used in resonant grounded power distribution networks to self‐extinguish powerline bushfires where the concepts of the proportional integral (PI) action and nonsingular fast terminal sliding surface (NFTSS) are combined togetherto utilize the benefits of both schemes. A hybrid sliding surface is designed for obtaining the control input so that the fault current compensation is achieved by the residual current compensation (RCC) inverter used within a REFCL to a value that the fire does not ignite. The inclusion of an integral action along with the NFTSS helps to significantly reduce the chattering effect.